2017
DOI: 10.1002/chem.201702894
|View full text |Cite
|
Sign up to set email alerts
|

[OsF6]x: Molecular Models for Spin‐Orbit Entangled Phenomena

Abstract: Heavy 5d elements, like osmium, feature strong spin-orbit interactions which are at the origin of exotic physical behaviors. Revealing the full potential of, for example, novel osmium oxide materials ("osmates") is however contingent upon a detailed understanding of the local single-ion properties. Herein, two molecular osmate analogues, [OsF ] and [OsF ] , are reported as model systems for Os and Os centers found in oxides. Using X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…[Co 3 (dpa) 4 OsF 6 ] · 2DMF ( 5 ) shows a temperature‐independent χT value between 100 and 300 K of 0.56 cm 3 K mol –1 , which is close to that expected for an S = 1/2 system with g = 2.40(5) (0.54 cm 3 K mol –1 ), as is typical for tricobalt EMACs. Upon cooling, a decrease of χT suggests weak antiferromagnetic interactions between the {Co 3 } magnetic sites through the virtually nonmagnetic [OsF 6 ] 2– linkers . A fit of the experimental susceptibility data of 4 to the Bonner–Fisher model for regular S = 1/2 chains on the basis of the Hamiltonian H ^ =2J i=1 N true S ^ i true S ^ i+1 gave values of g = 2.45(5) and J/k B = –1.9(4) K. In this case, [OsF 6 ] 2– mediates slightly stronger antiferromagnetic interactions than those previously found in 1 or 2 through [ZrF 6 ] 2– [ J/k B = –1.0(2) K] or [SnF 6 ] 2– units [ J/k B ≈ ±0.0(5) K] …”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…[Co 3 (dpa) 4 OsF 6 ] · 2DMF ( 5 ) shows a temperature‐independent χT value between 100 and 300 K of 0.56 cm 3 K mol –1 , which is close to that expected for an S = 1/2 system with g = 2.40(5) (0.54 cm 3 K mol –1 ), as is typical for tricobalt EMACs. Upon cooling, a decrease of χT suggests weak antiferromagnetic interactions between the {Co 3 } magnetic sites through the virtually nonmagnetic [OsF 6 ] 2– linkers . A fit of the experimental susceptibility data of 4 to the Bonner–Fisher model for regular S = 1/2 chains on the basis of the Hamiltonian H ^ =2J i=1 N true S ^ i true S ^ i+1 gave values of g = 2.45(5) and J/k B = –1.9(4) K. In this case, [OsF 6 ] 2– mediates slightly stronger antiferromagnetic interactions than those previously found in 1 or 2 through [ZrF 6 ] 2– [ J/k B = –1.0(2) K] or [SnF 6 ] 2– units [ J/k B ≈ ±0.0(5) K] …”
Section: Resultsmentioning
confidence: 79%
“…[Co 3 (dpa) 4 Cl 2 ] · x CH 2 Cl 2 was prepared as reported previously . [PPh 4 ] 2 [MF 6 ] · 2H 2 O (M = Ir, Os) were prepared by the respective literature procedures. The crystals of [PPh 4 ] 2 [MF 6 ] · 2H 2 O were dried under vacuum (10 –3 Torr) at 80 °C overnight before use to eliminate the water molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the magnitude of the magnetic moment in UO 2 could only be explained by invoking dynamic Jahn-Teller couplings, [25] and the inelastic neutron scattering spectra of the lowest-lying crystal field states of UF 4 and UCl 4 have revealed the signatures of strong couplings between electronic states and vibrations. [27] These significant spin and orbital components should be considered in the future analyses of the magnetic exchange interactions in uranium(IV)-based materials and fuel the curiosity for af undamental understanding of the electronic structure and magnetism of other actinide-containing molecules and materials. Despite the very weak total magnetic moment of [UF 6 ] 2À ,t he detailed study and analysis of its magnetic properties combining state-of-the-art X-ray absorption spectroscopy,m agnetometry,a nd quantum chemical calculations have demonstrated the existence of relatively large spin and orbital magnetic moments.T hese moments are roughly one hundred times larger than those found in related 5d systems with electronic singlet ground states.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Both anions can be of relevance for the urban mining processes [10,11] and the analytical chemistry of osmium [12,13]. Furthermore, the recent investigations showed that both species can be treated as model systems for investigating spin-orbit entangled phenomena in complexes with Os 4+ and Os 5+ atoms [14].…”
Section: Introductionmentioning
confidence: 99%